1999
DOI: 10.1086/302426
|View full text |Cite
|
Sign up to set email alerts
|

Calpainopathy—A Survey of Mutations and Polymorphisms

Abstract: Limb-girdle muscular dystrophy type 2A (LGMD2A) is an autosomal recessive disorder characterized mainly by symmetrical and selective atrophy of the proximal limb muscles. It derives from defects in the human CAPN3 gene, which encodes the skeletal muscle-specific member of the calpain family. This report represents a compilation of the mutations and variants identified so far in this gene. To date, 97 distinct pathogenic calpain 3 mutations have been identified (4 nonsense mutations, 32 deletions/insertions, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 34 publications
(33 reference statements)
5
141
1
6
Order By: Relevance
“…In terms of clinical presentation, our study confirms and further delineates the picture previously reported in several earlier studies 2, 3, 21, 22, 23, 24, 25, 26. Muscle weakness, which is remarkably symmetrical, is predominant in the axial muscles of the trunk and proximal muscles of the lower limb.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In terms of clinical presentation, our study confirms and further delineates the picture previously reported in several earlier studies 2, 3, 21, 22, 23, 24, 25, 26. Muscle weakness, which is remarkably symmetrical, is predominant in the axial muscles of the trunk and proximal muscles of the lower limb.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the fact that predominant mutations are null mutations prevents our cohort to truly represent the real genetic spectrum of calpainopathy. Indeed, the percentage of null alleles in Centers 2 (78%) and 3 (90%) exceeds what was previously reported (about a third of calpain 3 null alleles in the Leiden database (www.dmd.nl) and 45% in a previous report 21. Since null mutations seem to have a higher deleterious effect than missense mutations, it is possible that clinical presentation reported here is more severe than the mainstream presentation of LGMD2A patients.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This great inter and intra family variability has already been described not only in LGMD2A patients 16 but also in LGMD patients in general. 1,2,5 Here we confirmed this observation in a large calpainopathy sample including a total of 42 patients that carry the same recurrent mutations.…”
Section: Clinical Findings and Calpain-3 Deficiencymentioning
confidence: 57%
“…16 Most of them (70%) represent private variants although particular mutations were found more frequently in some populations. In addition six other mutations were identified exclusively in LGMD2A patients from Japan.…”
Section: Introductionmentioning
confidence: 99%